Pendekatan Berbasis Budaya Mutu (Quality Culture) dalam Menyikapi Dinamika Perubahan di SMP Negeri 37 Sinjai - Mustabsyirah, Mustabsyirah; Hasan, Mardhiah; Ramli, Bustan (ARZUSIN, 2025)
This article discusses the implementation of a quality culture-based approach in addressing the dynamics of change at SMP Negeri 37 Sinjai. This research aims to analyze the strategy, the application of discipline and responsibility values, and the obstacles faced in building a culture of quality in schools. The research was conducted using a qualitative method with a case study approach. Data were obtained through semi-structured interviews with the school principal and the head of curriculum, focusing on experiences and perspectives regarding the implementation of a quality culture. The results showed that the school's vision and mission are oriented towards the formation of a generation with character, excellence in achievement and global competitiveness. The implementation of quality culture is carried out through competency-based programs, technological innovation, religious activities, as well as habituation of disciplinary values and responsibilities that are strengthened by a system of sanctions and rewards. Teachers act as role models and mentors, while students are trained to practice these values in their daily activities. This strategy has proven effective in creating a conducive educational environment, improving the quality of learning and building responsible and disciplined student characters. The implementation of a quality culture at SMP Negeri 37 Sinjai supports the creation of quality and sustainable education. There is a need to strengthen teacher training, regular evaluation systems and the use of technology to support learning innovation. A collaborative approach involving all stakeholders is essential to ensure the success of a holistic quality culture.